LOW-MODULUS ARCTIC CABLE MATERIALS. - Kell, R. M.; Bennett, Bailey; Stickney, P. B. (1965)
Work was completed on a program to develop more flexible insulation and jacketing for coaxial cable. A blend consisting of equal parts of a high-density ethylene copolymer with a high-molecular weight polyisobutylene was selected as the most promising material for insulation. A recently developed polyether polyurethane exhibited the best over-all properties among available materials for jacketing. Two experimental polyether polyurethanes exhibited greater flexibility at low temperature, but are not commercially available. Efforts are in progress to prepare coaxial cable using the two most promising insulating and jacketing materials for evaluation under simulated service conditions. (Author)